Aplikasi Sistem Pakar Diagnosis Specific Learning Disability Menggunakan Metode Naïve Bayes Berbasis Game - Andreswari, Desi; Coastera, Funny Farady; Tiara Sella, Miranda (Universitas Bengkulu, 2024)
This research aims to develop a game-based expert system application for the diagnosis of Specific Learning Disability (SLD) using the Naïve Bayes method. SLD is a learning disorder that affects an individual’s academic skills in one or more areas, such as reading, writing,or mathematics. In effort to enchance the efficiency of SLD diagnosis, this application utilizes the Naïve Bayes method, a classification technique based on probability. The application is designed in the form of an interactive game to capture the user’s attention, particularly children who may be experiencing SLD. By combining gaming elements with the diagnostic process, it expected that users can be more engaged in the evaluation without compromising the educational aspect. The Naïve Bayes method is employed to generate diagnostic predictions based on information input by the user through a series of questions and tasks integrated into game. This research was conducted by testing 15 test data, and resulted in a system accuracy of 100%. Thus, this application can serve as a tool for early identification of SLD in children. It is anticipated that the development of this application can make a positive contribution to the field of education, particularly in supporting the identification and intervention processes for individuals experiencing SLD.